Economic crisis and the future of European integration: preliminary thoughts / A crise econômica e o futuro da integração Europeia: considerações preliminares - Lazarou, Elena (Mural Internacional, 2011)
The global financial crisis led to high levels of unemployment, a drop in structural growthand excessive levels of debt in Europe. An ageing population and increasing dependence on resources aggravated the crisis. Most importantly,and contrary to some expectations, the impact of the crisis varied significantly from state to state and between the North and South of the Union. The implications for the stability and solidarity of the unification process were inevitable: in less than two years, the gap between the donors and recipients within the EU grew, bringing with it pessimistic forecasts for the future of regional integration and alack of support for the EU in many member-states.The varying levels of damage among EU states illustrated the undoubted risks and obligations that stem from integration, and particularly from monetary unification. At the time of writing, the EU and especially its south, is still struggling to win the battle against the crisis. RESUMO A crise financeira global levou a altos patamares de desemprego, a queda do crescimento estrutural e níveis de dívida exorbitantes na Europa, sendo agravada pelo envelhecimento da população e o aumento da dependência nas reservas. É de se destacar que, ao contrário de algumas expectativas, o impacto da crise variou consideravelmente de um Estado para outro e entre o norte e o sul da União Europeia (UE). As implicações para a estabilidade e solidariedade do processo de unificação foram inevitáveis: em menos de dois anos, a distância entre doadores e beneficiários na UE aumentou, trazendo com ela previsões pessimistas sobre o futuro da integração regional e a ausência de apoio à UE em muitos países-membros. Os diferentes níveis de prejuízos nos Estados da UE ilustraram os riscos e obrigações inegáveis que decorrem da integração, principalmente da unificação monetária. Na época da redação deste artigo, a UE, sobretudo sua região sul, ainda lutava para vencer a batalha contra a crise. Keywords: European Union, Eurozone crisis, perspective to the EU. Palavras-chave: European Union, Crise da Eurozona, perspectivas para a EU. DOI: http://dx.doi.org/10.12957/rmi.2011.5830